Knowledge, Skills, And Devices: A Review Of Paramedics’ Familiarity With Cardiopulmonary Resuscitation Equipment In Pre-Hospital Care (The Review of Diabetic Studies, 2025)
Cardiopulmonary resuscitation (CPR) is a cornerstone of emergency medicine, and paramedics often serve as the first responders in out-of-hospital cardiac arrest cases. The effectiveness of CPR is increasingly influenced by the use of mechanical devices and adjunctive technologies, such as automated external defibrillators (AEDs), mechanical chest compression systems (e.g., LUCAS, AutoPulse), and airway management tools. Familiarity with these devices, including training, frequency of use, and confidence levels, is critical for optimizing patient outcomes. This review explores the current evidence on paramedics’ knowledge and skills in using CPR devices, the barriers to device adoption, and the clinical implications of familiarity for survival rates and neurological outcomes. By synthesizing existing literature, the review highlights training methodologies, systems of care integration, and the importance of continuous professional development. The findings suggest that high familiarity and competence improve performance during resuscitation, reduce human error, and enhance overall quality of pre-hospital care. Future directions include developing standardized training modules, leveraging simulation-based education, and integrating digital feedback systems into paramedic practice.